Eccentric exercises combined with electrical stimulation in the treatment of jumper's knee: a study on six high level jumping athletes - Basas Garcia, A.; Lorenzo, A.; Gómez-Ruano, M. A.; Fernández Jaén, T.; Álvarez Rey, G. (British Journal of Sports Medicine, 2013)
Introduction Treatment of patellar tendinopathy (PT)/Jumper's knee (JK) is known to be difficult, and there is no treatment of choice. This work analyses the development of a protocol using eccentric exercises and electrical stimulation, both using maximum tendon loading, to treat elite athletes suffering from Jumper's knee. Methods Six high level jumping athletes with chronic painful PT/JK completed a 6-month treatment/training programme using eccentric exercises and electrical stimulation. The protocol was done12 weeks in the winter pre-season and 10 weeks in the summer pre-season, for all together 36 months. Pain during patellar tendon loading activity was evaluated on a VAS, before the first session and then every 6 months. Results The VAS average fell significantly when the initial measurement is compared with those at 18, 24 and 48 months (p<0.01). There were no significant differences between the other comparisons, although they always improved when the protocol was followed and worsened following interruption of the latter (p>0.05). Discussion In a small group of high level jumping athletes with chronic painful PT/JK, eccentric exercises combined with electrical stimulation showed promising clinical results with significant pain reduction during tendon loading activity.